Pharmacognostic Evaluation, Chemical Characterization, and Antibacterial Activity of Bassia indica (Wight) A.J. Scott - Fayyaz Anjum; Saad Touqeer; Muhammad Younus Khan; QurratUlAin Jamil; Ayesha Rida; Jafir Hussain Shirazi; Syeda Abida Ejaz; Hafiz Muhammad Attaullah; Ghulam Sarwar; Zaeem Hayat Khan; Muhammad Asif Wazir; Barizah Malik; et al. (Plants, 2024)
Bassia indica (Wight) A.J. Scott is an Indian origin plant with documented medicinal and nutritional value, but has not been fully characterized yet. The present study was designed to establish pharmacognostic standards for the proper identification of the B. indica plant and its chemical characterization. The plant was standardized with World Health Organization (WHO) standardization tools and chemically characterized by Fourier transform infrared spectroscopy (FTIR) and gas chromatography-mass spectroscopy (GC-MS) analysis. Antibacterial potential was assessed by the zone of inhibition and minimum inhibitory concentration (MIC), and molecular docking studies were also performed. Pharmacognostic evaluation established the macroscopic and microscopic parameters for the identification of whole plant and its powder. Physicochemical parameters were also set forth while quantitative phytochemical analysis showed that the ethyl acetate fraction had the highest quantity of phenols, flavonoids, and tannins. FTIR analysis showed several functional groups such as phenols, alkanes, and alcohols while 55 phytochemicals were identified in the GC-MS analysis of the crude fraction. The crude extract and other fractions showed marked antibacterial activity, while the ethyl acetate fraction showed the least MIC (1.95–31.25 mg/mL). Phytochemicals identified in the GC-MS showed good molecular docking interactions against the DNA gyrase subunit B of bacteria with binding energies ranging from −4.2 to −9.4 kcal/mol. The current study describes the pharmacognostic characterization and phytochemical profiling of B. indica and provides scientific evidence to support its use in infections.